African Criminal Court : a commentary on the malabo protocol - Werle, Gerhard; Vormbaum, Moritz (The Hague : Asser Press, 2017)
"This book offers the first comprehensive and in-depth analysis of the provisions of the Malabo Protocol (the amendment protocol to the Statute of the African Court of Justice and Human and Peoples' Rights) adopted by the African Union at its 2014 Summit in Malabo, Equatorial Guinea. The Annex to the protocol, once it has received the required number of ratifications, will create a new Section in the African Court of Justice and Human and Peoples' Rights with jurisdiction over international and transnational crimes, hence an African Criminal Court. In this book, leading experts in the field of international criminal law analyze the main provisions of the Annex to the Malabo Protocol"--Back cover.
$t Creating an African Criminal Court / $r Gerhard Werle and Moritz Vormbaum -- $t Historical and Political Background to the Malabo Protocol / $r Ademola Abass -- $t Genocide (Article 28B), Crimes Against Humanity (Article 28C), War Crimes (Article 28D) and the Crime of Aggression (Article 28M) / $r Kai Ambos -- $t Crime of Unconstitutional Change of Government (Article 28E) / $r Gerhard Kemp and Selemani Kinyunyu -- $t Piracy (Article 28F), Terrorism (Article 28G) and Mercenarism (Article 28H) / $r Florian Jessberger -- $t Corruption (Article 28I) and Money Laundering (Article 28Ibis) / $r Lovell D. Fernandez -- $t Trafficking in Persons (Article 28J) and Trafficking in Drugs (Article 28K) / $r Fatuma Mninde-Silungwe -- $t Trafficking in Hazardous Wastes (Article 28L) and Illicit Exploitation of Natural Resources (Article 28Lbis) / $r Martin Heger -- $t Modes of Responsibility (Article 28N), Individual Criminal Responsibility (Article 46B) and Corporate Criminal Liability (Article 46C) / $r Chantal Meloni -- $t Preconditions to the Exercise of Jurisdiction (Article 46Ebis), Exercise of Jurisdiction (Article 46F) and the Prosecutor (Article 46G) / $r Volker Nerlich -- $t Complementary Jurisdiction (Article 46H) / $r Harmen Wilt -- $t Immunities (Article 46Abis) / $r Dire Tladi.
Includes bibliographical references and index.
Keywords: African Court on Human and Peoples' Rights; African Union. -- Assembly -- (2014 June 27); African Court on Human and Peoples' Rights; African Union. -- Assembly; Protocol on Amendments to the Protocol on the Statute of the African Court of Justice and Human Rigghts (2014 June 27) -- v Congresses; International law and human rights -- Africa; International law and human rights; International criminal courts -- Congresses. -- Africa; International crimes -- Congresses. -- Africa; International law and human rights -- Congresses. -- Africa; Africa; Conference papers and proceedings